Edukasi Dan Pencegahan Stunting Bersama Mahasiswa Kukerta UNRI Di Kampung Buatan II, Kecamatan Koto Gasib, Kabupaten Siak - Fachri Harisy; Zacki Alvandra Dwitama; Adinda Nathania Pratiwi; Putri Indri Daviani; Benita Graciela Simanungkalit; Nadya Fitri Syafira; Dea Safitri; Zikri Alfaridho; Venda Mirandah; Astrid Judika Simanjuntak (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2023)
Real work lectures (KUKERTA) are a form of student service to society. One form of service carried out is providing education to the community regarding the problem of stunting, especially to pregnant women and mothers with toddlers. This activity takes the form of education regarding stunting, characteristics of symptomatic children, prevention methods, outreach regarding immunization, measuring BMI in children and providing additional food in the form of boiled eggs and chicken porridge. This activity is in collaboration with Posyandu Melati Village Artificial II cadres and Koto Gasib Health Center health workers.